(3GdeTcdGJ GdbGfhfjI dYbhO GdJLGQI GdGdcJQhfjI (B:s (3ef MjK GdGKHGJ h JMOjO ReGf h ecGf GdYbO (B/s - (3GdYfRj, RjGO Ndjas ((3YeGf(B: s (3OGQ hGFd(B, s, 2009)
(3eGgjI GdJLGQI GdGdcJQhfjI , GKHGJ GdYbIO GdJj JJe YHQ GdGfJQfjJ (B: (3GdTQhW GdhGLH JhGaQgG aj GdeMQQ GdcJGHj h eOi JhGaQgG aj GdeMQQ GdGdcJQhfj h cPdc aj GdJhbjY h GdJhbjY GddcJQhfj , MLjI GdeMQQGJ GdGdcJQhfjI aj GdGKHGJ , ReGf h ecGf GdYbhO GdJj JJe YHQ GdGfJQfjJ (B: (3ReGf GdYbO YfO GdJYGbO Yf WQjb GdGfJQfJ , ecGf GHQGe GdYbO YfO GdJYGbO Yf WQjb GdGfJQfjJ (B.s
(3eQGLY U(B.197 (3; edGMb U(B.177s
Keywords: (3GdJLGQI GdGdcJQhfjIs; (3GdJLGQI GdOhdjIs; (3GdYbhO GdJLGQjIs